(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2018)
Background: Keloid is an area of overgrowth of fibrous tissue that usually develops after healing of skin injury and extends beyond the original defect. The existing treatment modalities include intralesional steroids, cryotherapy, silicone gel sheets, verapamil and 5- fluorouracil (5-FU). Methods: An open label study on 48 keloids in 35 subjects attending the Department of Dermatology in Dhaka Medical College Hospital during June 2017 and November 2017. Patients with keloids of 10cm and less along the longest diameter in the age group 18-75 years, Keloids with signs of infection, History of hypersensitivity and/or intolerance to 5- FU were included in the study. Results: Majority 21(60.0%) patients had single site keloid and 14(40.0%) had multiple site keloid. Majority 54.3% patients had keloids size 2-5 cm. All patients had pain and hyperpigmentation, 5(14.3%) had pustules, 3(8.6%) had necrosis and 1(2.9%) had ulceration. The median keloid area before the treatment was 4 with an inter quartile range of 1.5 to7.8 and this is compared with post treatment area, median 1.5 and inter quartile range 0.6 to 4. Wilcoxon signed rank test was used to assess the reduction in the size of keloid before and after treatment which was significant (P<.001). Conclusion: Majority patients had single site keloid. All patients had pain and hyperpigmentation. low dose intralesional 5-FU is safe and effective modality in the treatment of keloids. Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (2): 46-49